Stolen women in Medieval England: rape, abduction, and adultery ; 1100 - 1500 - Dunn, Caroline (Cambridge studies in medieval life and thought, 2013)
"This study of illicit sexuality in medieval England explores links between marriage and sex, law and disorder, and property and power. Some medieval Englishwomen endured rape or were kidnapped for forced marriages, yet most ravished women were married and many 'wife-thefts' were not forced kidnappings but cases of adultery fictitiously framed as abduction by abandoned husbands. In pursuing the themes of illicit sexuality and non-normative marital practices, this work analyses the nuances of the key Latin term raptus and the three overlapping offences that it could denote: rape, abduction and adultery. This investigation broadens our understanding of the role of women in the legal system; provides a means for analysing male control over female bodies, sexuality and access to the courts; and reveals ways in which female agency could, on occasion, manoeuvre around such controls"--